SPORTS DIPLOMACY SEBAGAI STRATEGI NATION BRANDING INDONESIA DALAM MENJADI TUAN RUMAH PIALA DUNIA U-17 2023 - Syafaatullah, Nazih; Rizki Tegar Sembada; Gilang Mukti Rukmana (CONVERGENCE: JOURNAL OF GLOBAL DYNAMICS, 2026)
The 2023 FIFA U-17 World Cup provided Indonesia with a strategic opportunity to strengthen its international reputation through sports diplomacy following challenges in hosting previous international football tournaments. This study aims to analyze how the successful organization of the 2023 FIFA U-17 World Cup contributed to Indonesia’s nation branding. The research employed a qualitative approach using explanatory analysis. Data were collected through library research based on secondary sources, including academic books, scholarly journal articles, official documents, and credible news reports. The findings reveal that the successful hosting of the tournament enhanced Indonesia’s image as a country capable of organizing an international sporting event in a professional, safe, and well-coordinated manner. This achievement was reflected in the readiness of sports infrastructure, effective inter-agency coordination, the promotion of national cultural identity through the Bacuya mascot, and positive international recognition of the event’s implementation. From a nation branding perspective, the most significant impacts were observed in the dimensions of tourism, governance, culture and heritage, and people. The study concludes that the 2023 FIFA U-17 World Cup served as an effective instrument of sports diplomacy in strengthening Indonesia’s positive international image and increasing global confidence in the country’s capacity to host major international sporting events.